1998
DOI: 10.1126/science.280.5361.298
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Termination of Transcription to Messenger RNA Maturation in Yeast

Abstract: The direct association between messenger RNA (mRNA) 3'-end processing and the termination of transcription was established for the CYC1 gene of Saccharomyces cerevisiae. The mutation of factors involved in the initial cleavage of the primary transcript at the poly(A) site (RNA14, RNA15, and PCF11) disrupted transcription termination at the 3' end of the CYC1 gene. In contrast, the mutation of factors involved in the subsequent polyadenylation step (PAP1, FIP1, and YTH1) had little effect. Thus, cleavage factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
228
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(238 citation statements)
references
References 24 publications
9
228
0
1
Order By: Relevance
“…Indeed, in vitro 39 processing reactions revealed that Pol II CTD significantly enhances this reaction, leading to the view that Pol II CTD itself acts as a component of the 39 processing machinery (Hirose and Manley 1998). Some cleavage/ poly(A) factors, as well as mediating 39-end processing, also aid subsequent Pol II termination (Birse et al 1998). A clear example is Pcf11, a component of CFII in mammals and CF1A in yeast.…”
Section: Polyadenylation Signals and 39 Noncoding Rna (Ncrna) Sequencesmentioning
confidence: 99%
“…Indeed, in vitro 39 processing reactions revealed that Pol II CTD significantly enhances this reaction, leading to the view that Pol II CTD itself acts as a component of the 39 processing machinery (Hirose and Manley 1998). Some cleavage/ poly(A) factors, as well as mediating 39-end processing, also aid subsequent Pol II termination (Birse et al 1998). A clear example is Pcf11, a component of CFII in mammals and CF1A in yeast.…”
Section: Polyadenylation Signals and 39 Noncoding Rna (Ncrna) Sequencesmentioning
confidence: 99%
“…This provides a signal for binding many factors involved in 39-end formation, which in turn renders RNAPII competent for termination (Whitelaw and Proudfoot 1986;Logan et al 1987;Connelly and Manley 1988;Birse et al 1997;. In yeast, mutations and conditional depletion of factors involved in pre-mRNA cleavage and polyadenylation, including homologs of CstF-64 (Rna15), CstF-77 (Rna14), Pcf11, CPSF160 (Yhh1), CPSF-73 (Ysh1), and Ssu72, result in read-through at the 39-end of protein-coding genes (Birse et al 1998;Dichtl et al 2002;Steinmetz and Brow 2003;Garas et al 2008). Accordingly, ChIP assays suggest that 39-end processing factors, including Pcf11, Rna14, and Rna15, become associated with the RNAPII EC at the poly(A) site, in a Ser2 phosphorylated CTD-dependant manner (Ahn et al 2004;Kim et al 2004a;Luo et al 2006).…”
Section: Trans-acting Factor Dynamics At the Poly(a) Site Affect Tranmentioning
confidence: 99%
“…In mammals, termination can occur anywhere from a few base pairs to several kilobases downstream from the 39-end of the mature RNA (Proudfoot 1989). RNAPII transcription termination is coupled to 39-end processing of the pre-mRNA (Birse et al 1998;Hirose and Manley 2000;Yonaha and Proudfoot 2000;Proudfoot 2004;Buratowski 2005), and an intact polyadenylation signal has long been known to be necessary for transcription termination of protein-coding genes in human and yeast cells (Whitelaw and Proudfoot 1986;Logan et al 1987;Connelly and Manley 1988).…”
mentioning
confidence: 99%
“…Mammalian CPSF (Dantonel et al 1997;McCracken et al 1997b) and CstF (cleavage stimulation factor; McCracken et al 1997b) associate with the CTD of RNA polymerase II and mutations in the CTD that prevent this association lead to disturbed transcription termination (McCracken et al 1997b). In addition, recent mutational studies in yeast have demonstrated that factors involved in pre-mRNA 3Ј-end cleavage are active in directing termination of transcription (Birse et al 1998).…”
mentioning
confidence: 99%